A review of agricultural extension roles in climate change adaptation and mitigation among farmers in Nigeria - Izuogu Chibuzo Uzoma; Oparaojiaku Joy Obiageli; Njoku Loveday Chukwudi; Ankrah Daniel Adu; Godwin Ominikari Abraham; Nwabuisi Chibudo Joshua (Agroznanje)
This review aims to provide an overview of agricultural extension roles in climate change adaptation and mitigation. It deals with farmers' access to extension services, roles of extension services, climate change-related training needs of extension personnel, the influence of extension contact on adopting climate change adaptation strategies, and constraints experienced by agricultural extension from existing empirical studies. Preferred Reporting Items for Systematic Reviews and Meta-Analyses was used to retrieve and analyse 78 studies. The majority (89.6%) of the studies have shown that farmers do not have access to climate change-related extension services. Extension services focused more on the transfer of information (98.2%), provision of technical advice (48.3%), and support of indigenous adaptation and mitigation strategies (32.6%). The main training needs of extension personnel were skills in the utilization of information and communication technologies (76.5%) and assessment and utilization of climate change-related farming technologies (45.7%). Extension contacts had a positive influence on climate change adaptation (95.7%), while the extension faced the challenges of poor funding (86.8%), inadequate manpower (76.4%), and lack of capacity (67.7%). The study concluded that agricultural extension plays an active role in climate change adaptation and mitigation and recommended more funding and capacity development should be provided for extension personnel. More studies are needed to identify the extent of the positive outcome of extension contact on climate change management among farmers.